Insider trading and networked directors - Goergen, Marc; Renneboog, Luc; Zhao, Yang (Journal of Corporate Finance, 2019)
We analyze the relation between insider trading and the networks of executive and non-executive directors in UK listed companies. While most existing studies focus on firm-specific private information, we find that non-firm-specific information – such as information on other companies and information on industry and market trends – plays an important role in insider trading behavior and performance. Well-connected directors trade shares less frequently and for smaller values. However, their transactions are more profitable, especially when they make consecutive opportunistic purchases in the multiple companies on whose boards they sit. Taken together, well-connected directors are likely to outperform their peers with inferior connections.